1991
DOI: 10.1093/glycob/1.2.155
|View full text |Cite
|
Sign up to set email alerts
|

The UDP-Glc:glycoprotein glucosyltrasferase is a soluble protein of the endoplasmic reticulum

Abstract: N-linked oligosaccharides devoid of glucose residues are transiently glucosylated directly from UDP-Glc in the endoplasmic reticulum. The reaction products have been identified, depending on the organisms, as protein-linked Glc1Man5-9GlcNAc2. Incubation of right side-sealed vesicles from rat liver with UDP-[14C]Glc, Ca2+ ions and denatured thyroglobulin led to the glucosylation of the macromolecule only when the vesicles had been disrupted previously by sonication or by the addition of detergents to the glucos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
27
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 0 publications
1
27
0
Order By: Relevance
“…Previously characterized eukaryotic selenoproteins were involved in redox processes (2), and redox function has been anticipated for Sep15, but the quality control of protein folding has not been linked to a redox process. (ii) UGTR is located in the ER (17), and no selenoprotein has yet been found to occur in this cellular compartment. In addition to Sep15, two other known mammalian selenoproteins, glutathione peroxidase 3 and selenoprotein P, contain N-terminal signal peptides.…”
Section: Figmentioning
confidence: 99%
“…Previously characterized eukaryotic selenoproteins were involved in redox processes (2), and redox function has been anticipated for Sep15, but the quality control of protein folding has not been linked to a redox process. (ii) UGTR is located in the ER (17), and no selenoprotein has yet been found to occur in this cellular compartment. In addition to Sep15, two other known mammalian selenoproteins, glutathione peroxidase 3 and selenoprotein P, contain N-terminal signal peptides.…”
Section: Figmentioning
confidence: 99%
“…Moreover, this result provided a convenient method for assaying the transferring enzyme (UDP-Glc:glycoprotein glucosyltransferase, GT), which was detected in microsomal membranes of mammalian, plant, fungal and trypanosomatid cells (27). Further work showed that GT was a soluble protein of the ER lumen and that the reaction products had the glucose unit linked to the same mannose with the same α(1,3) bond as in Glc 1 Man 9 GlcNAc 2 -P-P-dolichol ( Figure 1) (27,28). As observed for thyroglobulin, other glycoproteins (phytohemagglutinin, soybean agglutinin, ribonuclease B) were not glucosylated unless they had been previously denatured (29).…”
Section: Protein Glycosylation and Oligosaccharide Processing In Trypmentioning
confidence: 99%
“…Upon release, the terminal glucose is cleaved by glucosidase II, producing a shortened glycan, Man 9 GlcNAc 2 , which can no longer bind the lectin chaperones. Incompletely folded or misfolded proteins after the first cycle of folding are recognized by UDP-glucose:glycoprotein glucosyltransferase (UGGT), which adds back a glucose residue to regenerate the monoglucosylated form for additional rounds of lectin chaperone-assisted refolding (6,7). By glucosylating misfolded proteins, UGGT plays an important role in preventing misfolded proteins from exiting the ER.…”
mentioning
confidence: 99%